The Effect Of Digital Learning Media Based On Augmented Reality With Assemblr Edu Application On Students' Critical Thinking Abilities In Social Studies Subjects Of Grade VIII SMPN 18 Gresik: Pengaruh Media Pembelajaran Digital Berbasis Augmented Reality Dengan Aplikasi Assemblr Edu Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran IPS Kelas VIII SMPN 18 Gresik - Girit Ningrum, Endang Wuluh (Jurnal Dialektika Pendidikan IPS, 2025)
This study aims to explain the effect of digital learning media based on Augmented Reality (AR) using the Assemblr Edu application on students' critical thinking skills in Social Studies (IPS). This research uses a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The subjects of the study were eighth-grade students at SMPN 18 Gresik, with class VIII F as the experimental group and class VIII G as the control group. Data collection techniques included critical thinking pre-test and post-test assessments, student response questionnaires, and documentation. The prerequisite test results showed that the data were normally distributed and homogeneous, making it appropriate to analyze using the Independent Sample T-Test. The t-test results showed a significance value of 0.000 (< 0.05), indicating a significant difference in critical thinking skills between the experimental and control classes. The average post-test score of the experimental class was 88.38, while the control class scored 81.25. In addition, the N-Gain test showed a score of 0.6561, which falls into the effective category (moderate to high). This indicates that digital learning media based on augmented reality using the Assemblr Edu application is quite effective in improving students' critical thinking skills. Beyond the quantitative data results, student responses also revealed that those who participated in learning using the Assemblr Edu application experienced a significant increase in critical thinking skills compared to students in the control group. AR-based learning media encouraged students to be more active in exploring the material, thinking analytically, and understanding the relationships between concepts more deeply. These findings support the use of interactive digital technology as an effective learning strategy to foster critical thinking skills and meet the demands of 21st-century education.